Quality matters: low-density lipoprotein electronegativity but not quantity determines mortality risk in acute coronary syndromes. (3rd October 2022) - Kraler, S; Wenzl, F A; Shen, M Y; Von Eckardstein, A; Raeber, L; Mach, F; Nanchen, D; Matter, C; Gencer, B; Camici, G G; Chen, C H; Akhmedov, A; et al.
Abstract: Background: Changes in the protein composition of low-density lipoprotein (LDL) particles induce a shift in their electronegativity, a phenomenon implicated in both pro-inflammatory and pro-atherogenic signalling (1). While high levels of LDL foster the build-up of atherosclerotic plaques, and as such the susceptibility for the development of acute coronary syndromes (ACS), LDL levels assessed at the time of presentation fail to associate with fatal events following the index event (2). Experimental data suggest that altered LDL electronegativity exerts functional effects on both the myocardium and vasculature (1, 3). Purpose: We aimed to study the association between LDL electronegativity, assessed at the time of acute presentation, and all-cause mortality following the index ACS. Methods: We designed a case-cohort study in 2'619 ACS patients prospectively recruited in the investigator-driven, multicentre SPUM-ACS study (ClinicalTrials.gov Identifier: NCT01000701). Plasma LDL levels were quantified at baseline and LDL was chromatographically resolved into 5 subfractions (L1-L5), with the L1/L5 ratio serving as a proxy for overall LDL electronegativity. By employing least-squares ordinary regression models determinants of plasma L1, L5, and the L1/5 ratio were studied, and the association with mortality of both LDL levels and its electronegativity were estimated using weighted Cox regression models. Results: Cases and controls showed similar lipid profiles, but distinct LDL electronegativity, demonstrated by an increase in the L1/L5 ratio in cases vs. controls (P<0.05; Fig. 1). The highest-ranked determinants of the L1/L5 ratio were total cholesterol, LDL, high-density lipoprotein, age and triglycerides. Higher L1/L5 ratios were associated with increased risk all-cause and cardiovascular death at both 30-day (adjusted [adj.] hazard ratio [HR], 2.35, 95% confidence interval [CI], 1.81–3.03, and 2.37, 95% CI, 1.83–3.07, per standard-deviation [SD] increase) and 1-year intervals (adj. HR, 1.88, 95% CI 1.43–2.46, and 1.81, 95% CI 1.36–2.42 per SD increase). In contrast, LDL levels were not associated with these outcomes, neither at 30-day (adj. HR, 1.20, 95% CI, 0.64–2.24, and 1.20, 95% CI, 0.64–2.56 per SD increase) nor 1-year intervals (adj. HR, 1.35, 95% CI, 0.69–2.63, and 1.25, 95% CI 0.56–2.78 per SD increase). These associations were independent of age, sex, cardiometabolic risk factors and baseline risk, as assessed by the updated GRACE score. When compared with established risk factors (hsTnT levels, BMI, Killip class, eGFR, LDL levels), the L1/L5 ratio superseded several risk factors as an independent predictor for fatal events following ACS (Fig. 2). Conclusions: In contemporary patients with ACS, LDL electronegativity independently predicts fatal events after the acute event, while LDL levels do not. Our results suggest that LDL quality rather than quantity provides predictive utility for premature death within 1 year after the index ACS. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science FoundationSwiss Heart FoundationTheodor-Ida Herzog StiftungFoundation for Cardiovascular Research – Zurich Heart House